Canadian Pediatric Endocrine Group extension to WHO growth charts: Why bother? - Lawrence, Sarah (Pulsus Group Inc, 2013)
The Canadian Pediatric Endocrinology Group (CPEG) has produced complementary growth curves based on the 2010 ‘WHO Growth Charts for Canada’. In response to concerns from CPEG members and the general paediatric community regarding the presentation of the WHO data, complementary curves were generated, which the authors believe will enhance clarity, reduce potential errors in classification and enable users to better track short-term changes, particularly for weight in older children. Specifically, these curves extend weight-for-age beyond 10 years of age, restore additional percentiles within the normal range, remove extreme percentiles and harmonize the choice of body mass index percentiles with adult definitions of overweight and obesity. All modifications followed strict WHO methodology and used core data from the United States National Center for Health Statistics. The curves retain the clean appearance of the 2010 Canadian curves and are available from the CPEG website (http://cpeg-gcep.net).